Aluminium alloys and nanocomposites manufactured via friction stirring and 3D printing processes - Du, Zhenglin (Nanyang Technological University, 2018)
In recent years, fabricating aluminium matrix composites (AMCs) reinforced with nanoparticles via Selective laser melting (SLM) has drawn attention due to the potential in improving mechanical properties. However, the formation of undesirable intermetallic phases and porosity defects are challenging to overcome. Also, joining of AMCs is also important for industrial applications. Friction stir welding (FSW) is a solid-state joining technique capable of producing good mechanical properties. This study paves the way for the fabrication of new novel AMCs via FSP as well as the joining of SLM fabricated AMCs. The main findings are: i. A new Al-based nano-composite reinforced with uniformly dispersed Al2O3 and carbon nanotubes (CNTs) have been successfully fabricated using FSP. Grain refinement was observed in friction stir processing with/ without the addition of nano-sized reinforcement particles. The presence of nano-sized reinforcement led to more pronounced grain refinement as pinning effect of the nano-particles have retarded the grain growth rate in the dynamic recrystallisation process. The micro-hardness and tensile strengths were increased significantly through the addition of Al2O3 and CNTs nanoparticles. In particular, the yield strength of the composites increased 70% compared with that of FSPed Al when both Al2O3 and CNTs were added in the matrix. Multiple reinforcements with different shapes can be an effective method to increase the tensile strengths, especially yield strength of metal matrix composites. ii. SLM fabricated AlSi10Mg, and AlSi10Mg-nAl2O3 composites were studied. The addition of nAl2O3 resulted in the increasing formation of porosity in SLM fabricated AMCs. Hence, higher laser energy input was required to improve the wettability properties. Columnar grain structure along the thermal gradient was observed. Significant grain refinement was achieved with the addition of nAl2O3 via Zener pinning effect by exerting pinning pressure. The use of AlSi10Mg has resulted in the fabrication of AlSi10Mg-nAl2O3 composites with superior mechanical properties compared to Al-nAl2O3 composites using pure aluminium. iii. FSW had successfully joined SLM fabricated AlSi10Mg parts together without the presence of welding defects with rotational speed = 1200 rpm, travel speed = 1 mm/s, tilt angle = 4.5°. Grain refinement was observed in the FSW region due to dynamic recrystallisation process together with a significant increase in the fraction of high-angle grain boundaries during FSW. Significant decreases in the hardness and tensile strength were observed in the weld region due to the precipitation of Si. The increase in rotation speed or reduction in travel speed increased in grain size and slight reduction of hardness. Ductility was improved after FSW, and tensile strength is comparable to FSW of AA6061-T6 rolled sheets. iv. FSW was successfully used to joined SLM fabricated AlSi10Mg and its composites together achieving fine grains in the FSW region. Agglomerated and sintered nAl2O3 was observed to have broken down and dispersed in the matrix after FSW. It was observed that the use of higher tool rotational speed resulted in larger grains. The addition of nAl2O3 contributed to finer grains and higher hardness due to Zener pinning effect. FSW can generate porosity-free welds while 18% porosity density was received from as-printed substrates. These favourable findings ascertained the feasibility of using FSW to join SLM fabricated Al-Al2O3 composites and contributed to the scientific knowledge that FSW can produce a weld with desirable results for actual applications.